A facile route to prepare porous M-type SrFe12O19 ferrites assisted by using carbon spheres: Structural and magnetic properties. (April 2022) - Wang, Fangyu; Ji, Jiaojiao; Cao, Chunxiang; Gong, Chengzhuan; Xia, Ailin; Zhang, Huiyan; Li, Hailing; Liu, Zhiyuan; Jin, Chuangui
Abstract: SrFe12 O19 ferrite nanoparticles and nanoscale carbon spheres were mixed and sintered at 1100 °C and 1200 °C to prepare porous SrFe12 O19 ferrites, and their structural and magnetic properties were studied. Single-phase porous SrFe12 O19 ferrite specimens can be obtained after sintering at both temperatures. It was found that most small pores were merged to larger holes after sintering at 1200 °C. A small number of carbon spheres could be favorable to improve the crystallinity and thus enhance the saturation magnetization, while too much carbon spheres could affect the crystallinity negatively and reduce the saturation magnetization greatly. With the increasing content of carbon spheres, the change of coercivity exhibited opposite trends for the two sintering temperatures due to its complicated mechanism. It was also found that the magnetic domains can traverse the holes formed in the specimens. Graphical abstract: Image 1 Highlights: Porous SrFe12 O19 were prepared assisted by using carbon spheres. A small content of carbon spheres helps to improve the saturation magnetization of porous SrFe12 O19 specimens. Small pores were merged to larger holes after sintering at 1200 °C. The magnetic domains can span the holes formed in the specimens.